Proceedings of the 9th International Joint Conference on Biomedical Engineering Systems and Technologies 2016
DOI: 10.5220/0005647001370141
|View full text |Cite
|
Sign up to set email alerts
|

Robustness to Sub-optimal Temperatures of the Processes of Tsr Cluster Formation and Positioning in Escherichia Coli

Abstract: Clustering and positioning of chemotaxis-associated proteins are believed to be essential steps for their proper functioning. We investigate the robustness of these processes to sub-optimal temperatures by studying the size and location of clusters of Tsr-Venus proteins in live cells. We find that the degree of clustering of Tsr proteins is maximal under optimal temperature. The data further suggests that the weakening of the clustering process in lower-than and higher-than optimal temperatures is not due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Recent studies showed that the nucleoid plays a central role in the spatial organization of plasmids (31,32) and unwanted protein aggregates (33,34) in the cytoplasm of E. coli, as well as in the choice of location of the cell-division septum (61). By showing how the nucleoid contributes to the spatial organization of sensory complexes, and thus to the functional response of E. coli populations to various external stresses (43,62,63), our study further supports the notion that the nucleoid is critical for generating heterogeneities and asymmetries in the cytoplasm of E. coli that are essential for intracellular spatial organization and, combined with cell division, for cell-to-cell diversity within lineages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies showed that the nucleoid plays a central role in the spatial organization of plasmids (31,32) and unwanted protein aggregates (33,34) in the cytoplasm of E. coli, as well as in the choice of location of the cell-division septum (61). By showing how the nucleoid contributes to the spatial organization of sensory complexes, and thus to the functional response of E. coli populations to various external stresses (43,62,63), our study further supports the notion that the nucleoid is critical for generating heterogeneities and asymmetries in the cytoplasm of E. coli that are essential for intracellular spatial organization and, combined with cell division, for cell-to-cell diversity within lineages.…”
Section: Discussionmentioning
confidence: 99%
“…The image analysis procedure included cell segmentation, lineage construction, detection and characterization of fluorescent spots (Tsr clusters) and nucleoids, and characterization of the spatial distributions of clusters and nucleoids. The various steps were performed using custom-made software that integrates components from the software MAMLE (41) and CellAging (42), along with the cluster-detection method proposed in (43).…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation